Can silver diamine fluoride be an alternative to aerosol-based dentistry during the COVID scenario? A retrospective analysis - Ruchi Singhal; Parul Singhal; Ritu Namdev; Shefali Negi (Wolters Kluwer Medknow Publications, 2021)
Background: Restrictions on routine dental procedures involving aerosols during COVID-19 have resulted in a significant increase in the suffering of pediatric patients. Aim: The study reported the alternative measures followed in our department using SDF during the COVID era when routine elective dental procedures were prohibited. Materials and Methods: The retrospective data of patients aged 2-13 years with carious molar teeth who were treated with silver diamine fluoride without (Group 1) or with (Group 2) caries excavation were collected. Results: One thousand and seventy-two patients (646 males and 426 females) with 2459 carious molar were treated. On follow-up assessment at 3 months, 28 teeth in Group 1 and 21 teeth in Group 2 showed progression of carious lesion using International Caries Detection and Assessment System (ICDAS II criteria). Out of these failure cases, 32 (1.8%) teeth were primary and 17 (2.5%) were permanent. Complete relief in sensitivity/pain on stimulation was reported in 2381 teeth (96.83%), whereas in 78 (3.17%) teeth, mild sensitivity/pain on stimulation was reported. The average time consumed during treatment per tooth in Group 1 was 5.04 min and in Group 2 was 5.78 min. Conclusion: SDF application can be carried out as a nonaerosol-generating procedure and is a simple technique for children and clinicians.